DAMPAK PANDEMI COVID-19 DALAM PELAKSANAAN PROYEK KONSTRUKSI DI PROVINSI ACEH - Teuku Syahirman; Muttaqin Hasan; Teuku Budi Aulia (Prodi Magister Teknik Sipil Unsyiah, 2023)
The implementation of construction projects in Aceh province since the beginning of 2020 until now has been impacted during the 2019 coronavirus disease (Covid-19) pandemic. One of the significant impacts is the disruption of the supply chain, which hinders the implementation of construction projects. Hence, it is necessary to conduct investigations to determine the dominant factors and factors affected by the Covid-19 pandemic in the implementation of construction projects in Aceh province. The construction projects audited are construction projects, roads, bridges, drainage, irrigation, reservoirs and weirs, to be completed by a construction company in Aceh Province using 2020 and 2021 sources of funding from the Aceh Revenue and Expenditure Budget of Aceh (APBA). were Research This method uses a mixed methods approach through a questionnaire. The respondents were addressed to the project manager/construction manager/supervisor of the executing company. The population of construction projects in Aceh province during the Covid-19 pandemic for 2020 and 2021 was 221 companies/packages, while the sample consisted of 165 companies/packages. A proportionally stratified random sample is used as the sampling method. The data analysis technique used descriptive statistics, validity testing, reliability testing, and PCA using Statistical Product and Service Solution (SPSS) software. The results showed that the factors influenced by the Covid-19 pandemic in the implementation of construction projects in Aceh province were 6 factors, namely area restrictions, implementation methods, project costs, physical distancing, insecurity and financial factors of the contractor with a Variance (percentage of use) of 59.104%. The dominant factor affected by the Covid-19 pandemic in the implementation of construction projects in Aceh province is the area constraint factor with a variance of 18.848%.